Aloha Undergraduates: Development and Application of Local & Indigenous Topics into an Undergraduate Public Health Curriculum - Nelson-Hurwitz, Denise C.; Kehl, Lisa; Braun, Kathryn L. (Frontiers in Public Health, 2019)
As public health education expands to include undergraduate students, it is important to include discussion of local public health topics and issues to provide a sense of place to the educational experience. Inclusion of Native Hawaiian and indigenous issues and perspectives is also an established priority of the University of Hawai‘i system. To address both needs, a required course was created during development of a new Bachelor of Arts (BA) public health program at the University of Hawai‘i at Mānoa to specifically focus on discussion of local and indigenous public health topics of interest. Public Health Issues in Hawai‘i is an introductory course included early in the recommended undergraduate curriculum and emphasizes the application of public health skills and principles to local issues, (e.g. state-level legislative awareness and local sustainability topics). The Public Health Issues in Hawai‘i course further challenges students to recognize public health practice in their daily activities, and encourages them to become actively engaged in local community issues early in their public health educational careers. Among multiple advantages, improved awareness of local health challenges and early connections to community members and organizations have been instrumental in actively engaging local students in their education, and has also proved beneficial for students participating in required undergraduate applied learning capstone experiences and entry-level public health careers following graduation. Here we present insights into course development, articulation with broader program curricula, and successes and challenges in the past four years of implementation and instruction.